Negotiating difference race, gender, and the politics of positionality - Awkward, Michael (Black literature and culture, 1995)
From Spike Lee's She's Gotta Have It to Michael Jackson's physical transmutations, from Toni Morrison's Song of Solomon to August Wilson's Fences, from male scholars' investments in feminism to white scholars' in black texts - Awkward explores cultural moments that challenge the exclusive critical authority of race and gender. In each instance he confronts the question: What do artists, scholars, and others concerned with representations of African American life make of the view that gender, race, and sexuality circumscribe their own and others' lives and narratives? Throughout he demonstrates the perils and merits of the sort of boundary crossing this book ultimately makes: a black male feminism